Eficiência agroeconômica do consórcio mamona e amendoim em área do semiárido paraibano - Dutra, Alexson Filgueiras (2012)
The castor bean has great importance to the brazilian semiarid region and it can be easy to grow, tolerant to drought and has beneficial features to production associated with other cultures. Thus, the objective of this study was to evaluate agricultural economic aspects intercropping castor and peanut under irrigated conditions in semiarid. The experiment was accomplished at the experimental Sector Fruit and Plant Ecophysiology, IV Campus, State University of Paraiba (UEPB), located in the municipality of Catolé do Rocha, PB. The study period was from June to December 2011, using the cultivation of castor bean BRS Energy and peanuts 'BR-1', in intercropping systems and isolated. The experimental design was in randomized blocks with four replications and eight treatments: T1- Single castor bean spaced in 2,0 m x 0,5 m, T2- Single peanut in spacing of 2,0 m x 0,2 m, T3- Single peanut spaced in 1,0 m x 0,2 m, T4- Consortium castor bean and peanuts sown on the same day, T5- Consortium castor bean and peanuts sown 10 days after the castor bean (M + A10), T6- Consortium castor bean and peanut, sown 15 days after castor bean (M + A15), T7- Consortium castor bean and peanut sown 20 days after the castor bean (M + A20), T8- Consortium castor bean and peanut sown 25 days after the castor bean (M + A25). The best growth rates and leaf area of the castor bean BRS Energy are obtained when the peanuts BR-1 was sown from 20 to 25 days after the castor bean. The production of peanut pods increased when was sown between 10 and 15 days after the castor bean. The later periods of sowing of peanuts will provide better yields of castor bean in intercropping system. In the consortium, the peanut is biologically more efficient and higher yields are obtained when sown 20 days after the castor bean.